Calderón y la reescritura de títulos de comedias - Sáez, Adrián J. (My University, 2015)
If rewriting is one of the identity signs of Calderón’s theatre, it is useful to start from the beginning and examine the occasional revision of his works’ titles, because this paratext is the principal presentation card of every text. In this way, this work analyzes the cases in where the title changes between two versions of the play (Amor, honor y poder, La devoción de la cruz, El mayor monstruo del mundo, Guárdate del agua mansa) in order to enquire the fonction of this variation, which could mean a new authorial intent and new perspectives of construction, approach and meaning.
Keywords: Pedro Calderón de la Barca; théâtre; Siècle d'Or; réécriture; titres.